Trikoepitelioma Multipel Familial: Laporan Kasus - Meilany Durry; Anggreiny Iwisara; Fera Mawu; Sthefanie Gaghana (e-CliniC, 2023)
Abstract: Trichoepithelioma is a benign tumor of folliculosebaceous-apocrine germ cell origin. There are three clinical variants of trichoepithelioma, as follows: solitary, multiple, and desmoplastic. The clinical features of trichoepithelioma are skin-colored papules up to 0.5 cm in size. with predilection areas on the nose, upper lip, and cheeks. The specific variant of familial multiple trichoepithelioma is inherited in an autosomal-dominant type and usually occurs in childhood and puberty. We reported a 36-year-old woman with complaints of skin-colored papules on the face and neck. There were family members with the same complaint. Histopathological examination showed skin tissue with dermal tumor consisting of basaloid cells arranged in palisade form in the periphery, and several horn-cysts among the cells that indicated a trichoepithelioma. The patient was planned to be treated with topical imiquimod and electric surgery. In conclusion, based on anamnesis, physical examination, and histopathological result, the diagnosis of this case was familial multiple trichoepithelioma. Keywords: trichoepitelioma; cylindromatosis; skin appendageal tumor; histopathological examination   Abstrak: Trikoepitelioma merupakan suatu tumor asal sel germinal folliculosebaceous-apocrine. Terdapat tiga varian klinis trikoepitelioma yaitu soliter, multipel, dan desmoplastik. Gambaran klinis trikoepitelioma ialah papula sewarna dengan kulit ukuran sampai 0,5 cm dan lokasi predileksi yaitu hidung, bibir atas, dan pipi. Terdapat satu varian spesifik yaitu trikoepitelioma multipel familial yang diwariskan secara dominan autosomal dan biasanya timbul pada masa kanak-kanak dan pubertas. Kami melaporkan seorang perempuan berusia 36 tahun dengan keluhan bintil-bintil sewarna kulit, multipel pada area wajah dan leher. Di dalam keluarga pasien terdapat anggota keluarga dengan keluhan yang sama. Hasil pemeriksaan histopatologik mendapatkan jaringan kulit dengan tumor pada dermis yang terdiri dari sel-sel basaloid, bagian tepi tersusun palisade, dan di antaranya tampak beberapa horn-cyst yang menunjukkan suatu trikoepitelioma. Pasien ini direncanakan diberikan terapi dengan imiquimod topical dan bedah listrik. Simpulan kasus ini ialah suatu trikoepitelioma multipel familial yang ditegakkan berdasarkan anamnesis, pemeriksaan fisik, dan pemeriksaan histopatologik. Kata kunci: trikoepitelioma; cylindromatosis; skin appendageal tumor; pemeriksaan histopatologik